2023
DOI: 10.1038/s41598-023-27514-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between action, social and multisensory spaces

Abstract: Several spaces around the body have been described, contributing to interactions with objects (peripersonal) or people (interpersonal and personal). The sensorimotor and multisensory properties of action peripersonal space are assumed to be involved in the regulation of social personal and interpersonal spaces, but experimental evidence is tenuous. Hence, the present study investigated the relationship between multisensory integration and action and social spaces. Participants indicated when an approaching soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Finally, the size of the PPS can also be modulated according to the social validity of the stimuli in the surrounding space. Geers and Coello 27 have recently found that when a human avatar was present, even if it was not interacting with the participant, their extent of reachable-space was significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the size of the PPS can also be modulated according to the social validity of the stimuli in the surrounding space. Geers and Coello 27 have recently found that when a human avatar was present, even if it was not interacting with the participant, their extent of reachable-space was significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual Reality (VR) set-ups offer an ideal environment to understand which aspects of the training plays a key role in inducing the reshaping of the PPS as it allows to design ecologically plausible looming visual stimuli. Indeed, previous reports suggest that the PPS can be successfully investigated with VR 27 , 29 – 31 . As it has been demonstrated for the audio-tactile task 28 , if the vibration is delivered when the virtual visual stimulus is perceived as being close to the participants body, reaction times (RTs) to the vibration are significantly reduced, and in some cases almost halved 29 .…”
Section: Introductionmentioning
confidence: 99%
“…, 1999 ; Graziano and Gross, 1993 ), in the so-called extrapersonal space. To note, the extrapersonal space is determined not only by arm’s reach but also by the brain’s representation of the extended body space ( Berti and Frassinetti, 2000 ), the nature of the stimuli and the type of interactions envisaged ( Geers and Coello, 2023 ). Human behavioral and neural studies [see, e.g., Maravita et al.…”
Section: Introductionmentioning
confidence: 99%
“…Taking together the approach of an object to the PPS and a multisensory interaction, it is possible that this interaction could be used to predict subsequent contact (tactile event) since the approaching object might subsequently contact the body. It is necessary to keep in mind that such visuo–tactile interaction in the PPS could vary flexibly, e.g., the facilitation effect of multisensory integration in the PPS could be extended to a wider space depending on the meaning of the visual stimuli and the social context (Geers and Coello, 2023 ). Therefore, the relationship between multisensory integration and interactions with the environment should be considered for each situation.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the safety margin, it is possible to predict subsequent contact at an early stage, before contact, by using the approach of visual stimuli. Furthermore, the facilitation effect of bimodal sensory stimulation on multisensory interactions varies flexibly and could occur even in spaces away from the body; thus, it might be possible to predict the contact of a tactile stimulus from the beginning of the approach of the visual stimuli (e.g., Serino et al, 2015a , b ; Bertoni et al, 2021 ; Geers and Coello, 2023 ). Considering finite cognitive resources, it is possible to allocate attentional resources just before contact (i.e., near the hand) to predict a tactile stimulus.…”
Section: Introductionmentioning
confidence: 99%